2018
DOI: 10.1186/s13045-018-0611-7
|View full text |Cite|
|
Sign up to set email alerts
|

Pin1 inhibition exerts potent activity against acute myeloid leukemia through blocking multiple cancer-driving pathways

Abstract: BackgroundThe increasing genomic complexity of acute myeloid leukemia (AML), the most common form of acute leukemia, poses a major challenge to its therapy. To identify potent therapeutic targets with the ability to block multiple cancer-driving pathways is thus imperative. The unique peptidyl-prolyl cis-trans isomerase Pin1 has been reported to promote tumorigenesis through upregulation of numerous cancer-driving pathways. Although Pin1 is a key drug target for treating acute promyelocytic leukemia (APL) caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 80 publications
(86 reference statements)
2
19
0
Order By: Relevance
“…Traditional prognostic tools and common therapeutic targets have not achieved satisfactory results in clinical studies of high intratumor heterogeneity in PDAC . Targeting PIN1, to block multiple signaling pathways, has been demonstrated to exhibit potent antitumor effects in tumors with poor prognosis but limited therapeutic efficiency in clinical practice . As for the devastating disease of PDAC, our present study indicated that PIN1 may be an attractive predictive marker and targeting PIN1 could exert potent antitumor activity.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Traditional prognostic tools and common therapeutic targets have not achieved satisfactory results in clinical studies of high intratumor heterogeneity in PDAC . Targeting PIN1, to block multiple signaling pathways, has been demonstrated to exhibit potent antitumor effects in tumors with poor prognosis but limited therapeutic efficiency in clinical practice . As for the devastating disease of PDAC, our present study indicated that PIN1 may be an attractive predictive marker and targeting PIN1 could exert potent antitumor activity.…”
Section: Discussionmentioning
confidence: 72%
“…Given that Pin1−/− homozygous mice grow normally and there are no general side effects on normal cells, PIN1 is a potential molecular target for cancer treatment. Notably, targeting of PIN1 has been achieving some promising results in animal studies on leukemia, triple negative breast cancer and hepatocellular carcinoma . However, little evidence on the function of PIN1 in the progression of PDAC has been seen.…”
Section: Introductionmentioning
confidence: 99%
“…ATRA binds and induces degradation of Pin1 and its substrate PML‐RARA and thereby exerts anticancer activity against APL in cell and animal models and human patients . This anticancer activity of ATRA has been confirmed and expanded to breast cancer, liver cancer even using a different ATRA controlled release formulation, and acute myeloid leukemia (AML), as well as in lupus and asthma . However, the role of Pin1 in mediating ATRA anticancer activity against gastric cancer is not known.…”
Section: Discussionmentioning
confidence: 99%
“…ATRA-induced Pin1 ablation also exerts antitumor activity against breast cancer by blocking multiple oncogenic pathways. The ability of ATRA to inhibit Pin1 function has been confirmed in breast cancer 24 , 39 and liver cancer 24 , 40 , 41 even using a different ATRA controlled release formulation 42 , and acute myeloid leukemia (AML) 43 , as well as in lupus 44 and asthma 45 . However, regular ATRA formulation has a half-life of only 45 min in humans 46 and biodegrabable longer half-life of ATRA formulations that might be used in humans are under development 42 .…”
Section: Introductionmentioning
confidence: 97%